MÔ HÌNH ĐỊA MÔI TRƯỜNG CỦA CÁC MỎ KHOÁNG VÀ Ý NGHĨA CỦA CHÚNG TRONG ĐÁNH GIÁ ẢNH HƯỞNG MÔI TRƯỜNG DO KHAI THÁC MỎ - Phổ, Nguyễn Văn; Xuân, Phạm Tích (Vietnam Journal of Earth Sciences, 2012)
Geoenvironmental models of mineral deposits and their significant in determining the effects of mining processes Geoenvironmental models are natural extensions of mineral deposit models. A geo-environmental model of a mineral deposit is a compilation of geologic, geochemical, geophysical, hydrologic and engineering information pertaining to the environmental behavior of geologically similar mineral deposits prior to mining, and resulting from mining, mineral processing, and smelting. So it provides information about natural geochemical variations associated with a particular deposit type, and geochemical variations associated with its mining effluents, wastes, and mineral processing facilities, including smelters. Geoenviromental models are best used as guidelines for potential ranges of environmental signatures that may apply to the site. Data include information about waters and solids, so the minimum background in geochemical concepts that are fundamental to geoenvironmental models. Brief descriptions of key elements of a geoenvironmental model are the salient features of categories on the point of view: each mineral deposit is unique unto itself, and each class of mineral deposit is also unique. The categories include; natural geographical conditions, geology of deposit, mineralogy and geochemistry of deposit, mining and ore processing methods. These categories may be changed in particular deposits, but some degree of flexibility must be maintained in the features considered essential for a given model.